Cell cycle dependence of ERK activation dynamics is regulated by PI3K and PAK1 signaling - Ryo Yoshizawa; Yasushi Sako (Scientific Reports)
Abstract Growth factor-induced RTK/RAS/MAPK signaling is crucial for cell cycle progression, including G1 to S and G2 to M phase transitions. However, the regulatory mechanism of MAPK (ERK) in the S–G2M phase remains unclear. In this study, we analyzed the nuclear translocation dynamics of fluorescently labeled ERK induced by EGF during cell cycle progression and simultaneously analyzed the membrane translocation dynamics of GRB2 and PI3K. The transient ERK dynamics in a population of cells with a high frequency of G0/G1 cells became sustained with the increase in S–G2M cells. The sustained localization of PI3K, rather than GRB2, showed a stronger correlation with nuclear ERK localization. PI3K-mediated PAK1 activation was essential for ERK translocation. EGFR/PI3K clusters frequently formed on the plasma membrane and were rapidly endocytosed in the high G0/G1 cell population, resulting in transient PI3K localization, whereas dispersed PI3K predominated in the high S–G2M cells, resulting in sustained PI3K localization. On the other hand, PAK1 remained on the plasma membrane. Our results suggest that the sustained spatial colocalization of PI3K and PAK1, particularly in the S–G2M phase, prolonged the PAK1 signaling for ERK activation. Sustained ERK activation was also correlated with a shorter time to cell division.